2017
DOI: 10.1021/acsami.6b15880
|View full text |Cite
|
Sign up to set email alerts
|

SnO2@PANI Core–Shell Nanorod Arrays on 3D Graphite Foam: A High-Performance Integrated Electrode for Lithium-Ion Batteries

Abstract: The rational design and controllable fabrication of electrode materials with tailored structures and superior performance is highly desirable for the next-generation lithium ion batteries (LIBs). In this work, a novel three-dimensional (3D) graphite foam (GF)@SnO nanorod arrays (NRAs)@polyaniline (PANI) hybrid architecture was constructed via solvothermal growth followed by electrochemical deposition. Aligned SnO NRAs were uniformly grown on the surface of GF, and a PANI shell with a thickness of ∼40 nm was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 65 publications
0
37
0
Order By: Relevance
“…In LIBs, conductive agents and electrically insulating binders added during electrode preparation do not contribute to its capacity, but rather give rise to a large interfacial charge‐transfer resistance as a result of increased grain boundaries having adverse effects on the electrochemical properties . Consequently, many researchers make great efforts to identify novel electronically conducting binders instead of the electrochemically inactive conductive carbon additives and non‐conductive binders.…”
Section: Applications Of Panimentioning
confidence: 99%
“…In LIBs, conductive agents and electrically insulating binders added during electrode preparation do not contribute to its capacity, but rather give rise to a large interfacial charge‐transfer resistance as a result of increased grain boundaries having adverse effects on the electrochemical properties . Consequently, many researchers make great efforts to identify novel electronically conducting binders instead of the electrochemically inactive conductive carbon additives and non‐conductive binders.…”
Section: Applications Of Panimentioning
confidence: 99%
“…In this work, the I 2D /I G value of the synthesized 3D graphene foam is 0.47, exhibiting that the prepared graphene has a multilayer structure . The strength of D band at 1350 cm −1 is very low, indicating that the graphene foam treated before HNO 3 is of high quality with very few defects, ensures fast transport of electrons . The treatment by HNO 3 at 100 °C for 10 h can introduce appropriate defects into the surface of 3D graphene foam.…”
Section: Resultsmentioning
confidence: 99%
“…In this architecture, the 3D graphite foam (GF) provides a large specific surface area and high electronic conductivity. The SnO 2 NRAs provide direct transfer pathways for the electrons and lithium ions; at the same time, the conductive polyaniline (PANi) shell effectively accommodates the large volume variation in SnO 2 during the electrode reactions . Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
“…The SnO 2 NRAs provide direct transfer pathways for the electrons and lithium ions; at the same time, the conductive polyaniline (PANi) shell effectively accommodates the large volume variation in SnO 2 during the electrode reactions. [26] Zhou et al reported PANi-encapsulated Si on a 3D carbon nanotube foam as the anode for LIBs. The authors utilized melamine as a template, which was carbonized to form carbon nanotubes, and then attached high-capacity silicon and deposited PANi.…”
Section: Introductionmentioning
confidence: 99%